Personality and temperament of Olympic taekwondo competitors and their level of advancement and sports performance - MARTA REMISZEWSKA; JERZY F. MILLER; MAREK GRACZYK; MILENA LACHOWICZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪The goal of the presented study was to identify personality and temperament traits of Olympic taekwondo competitors at a varied level of advancement in relation to their sports performance. Material and methods: ‪There were 127 Olympic taekwondo competitors in a junior category (n = 63) and a senior one (n = 64) who were divided into two research groups, i.e. competitors who won medals and competitors who did not win medals in the Polish championship of Olympic taekwondo. Results: H‪aving analysed the data, it turned out that the two researched groups (juniors and seniors) were similar regarding a low level of anxiety and neuroticism, a high level of extroversion and an average level of agreeableness. The only variable significantly differentiating competitors in junior and senior groups was neuroticism. Conclusions: ‪In the junior group, it was extroversion that differentiated the competitors with or without medals, in the senior one - agreeableness.